2021
DOI: 10.3847/2041-8213/abdf5a
|View full text |Cite
|
Sign up to set email alerts
|

Indication of a Pulsar Wind Nebula in the Hard X-Ray Emission from SN 1987A

Abstract: Since the day of its explosion, SN 1987A (SN87A) was closely monitored with the aim to study its evolution and to detect its central compact relic. The detection of neutrinos from the supernova strongly supports the formation of a neutron star (NS). However, the constant and fruitless search for this object has led to different hypotheses on its nature. To date, the detection in the Atacama Large Millimeter/submillimeter Array data of a feature that is somehow compatible with the emission arising from a proto-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Recently, NuSTAR observations of SNR 1987A showed evidence for hard X-ray emission up to E ∼ 20 keV (Alp et al 2021;Greco et al 2021). The NuSTAR-detected hard X-ray spectrum may be attributed to either nonthermal (PL with photon index Γ ∼ 2.5, Greco et al 2021) or thermal (kT ∼ 4 keV, Alp et al 2021) origins.…”
Section: Hard X-rays From Snr 1987amentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, NuSTAR observations of SNR 1987A showed evidence for hard X-ray emission up to E ∼ 20 keV (Alp et al 2021;Greco et al 2021). The NuSTAR-detected hard X-ray spectrum may be attributed to either nonthermal (PL with photon index Γ ∼ 2.5, Greco et al 2021) or thermal (kT ∼ 4 keV, Alp et al 2021) origins.…”
Section: Hard X-rays From Snr 1987amentioning
confidence: 99%
“…These multi-wavelength observations show that the remnant of SN 1987A is now entering a new phase, where the blast wave has started probing outside the ER, while the reverse shock may be closing in on the metal-rich ejecta towards the center. Recently, NuSTAR observations of SNR 1987A have showed evidence for hard X-ray emission up to E ∼ 20 keV (Greco et al 2021;Alp et al 2021). While its origins are still unclear, either nonthermal (Greco et al 2021) or thermal (Alp et al 2021) origins have been suggested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For a review of the insights gained in the decades of observation, see . The neutron star itself has not definitively been found yet due to high extinction by the ejecta (Orlando et al 2015;Alp et al 2018), although some authors (Zanardo et al 2014;Cigan et al 2019;Greco et al 2021) have reported signs of a possible neutron star remnant (but see also Alp et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The associations between the pulsars and supernova remnants (SNRs) have been of considerable interest topics in neutron stars (NSs) astrophysics, since the radio pulses were firstly observed in the Crab Nebula in 1968 (Staelin & Reifenstein 1968), as well as the discovery of the Vela pulsar (Large, Vaughan, & Mills 1968). The story is continuing with identifying the potential NS in SN 1987A (Page et al 2020;Greco et al 2021;Soker 2021). Thanks the efforts and developments of astronomical facilities in recent years, the number of pulsars and SNRs has increased significantly.…”
Section: Introductionmentioning
confidence: 99%